Bedside monitoring of free flaps using ICG-fluorescence angiography significantly improves detection of postoperative perfusion impairment##. Issue 3 (4th May 2019) - Adelsberger, Rosmarie; Fakin, Richard; Mirtschink, Sophia; Forster, Natasha; Giovanoli, Pietro; Lindenblatt, Nicole
Abstract: After microvascular tissue transfer, free flaps require meticulous postoperative surveillance. The purpose of this study was to evaluate the effect and applicability of indocyanine green fluorescence angiography (ICG-FA) in bedside monitoring of free flaps postoperatively, especially considering its role in correctly identifying vascular thromboses. Between February 2012 and October 2015, 210 free flaps used for defect reconstruction were analyzed. The flaps were monitored bedside for flap perfusion compromise by clinical examination and by ICG-FA in a standardized procedure in the first 3 postoperative days. Data were evaluated retrospectively with respect to the etiology of the perfusion compromise with special focus on vascular thromboses and revision rates. In total, 23 vascular thromboses were identified. The combination of clinical examination and ICG-FA (85%) was most successful in determining the prevalence of vascular thromboses. In 41 cases, clinical and/or ICG-FA examinations indicated revision surgery. The flap salvage rate after revision was 77% (31 cases), which results in an overall flap survival rate of 96%. The revision rates were reduced over the study time from 22% in 2012 to 12% in 2015. ICG-FA as an adjunct to clinical examination of free flaps can help in correctly identifying vascular thromboses and can help decide if revision surgery is necessary in not obvious cases of perfusion compromise.